PHILOSOPHICAL ISSUES IN JALALUDDIN RUMI’S VIEWS (World Bulletin of Social Sciences, 2025)
This article discusses the works of Jalaluddin Rumi, his writings, and his views on philosophical issues. In particular, it explores Rumi’s place in Sufi philosophy and the main ideas of his works